Evaluation Model of Internal Quality Assurance System in Universities - Elbadiansyah Elbadiansyah; Masyni Masyni (STAI Hubbulwathan Duri, 2022)
This study aims to determine: 1) implementation of internal quality management evaluation, 2) development of an evaluation model, 3) testing a new model of internal quality evaluation in the quality cycle, and 4) the effectiveness of the implementation of the internal quality management evaluation model that has been implemented at the university. Methods This research uses a qualitative approach with types. Data collection techniques are carried out through in-depth interviews, participant observation, photography and documentation. The data were analyzed using the model of Miles and Huberman's interactive transformation consisting of data collection, data reduction, data display and conclusion. The validity of the data is done by testing the credibility, transferability, dependability, and confirmability. This study found that first, the internal quality management evaluation model used by three universities was PPEPP (Determination, Implementation, Evaluation, Control, Improvement). Second, creating an evaluation model based on AIS (Academic Information System) and the Higher Education Database (PD Dikti). And third, testing a new model of internal quality evaluation in the quality cycle, namely monitoring and evaluation, recording and inspection, and action.